2018
DOI: 10.1007/s00442-018-4128-0
|View full text |Cite
|
Sign up to set email alerts
|

Colour polymorphism in owls is linked to light variability

Abstract: Owls show an astonishing variation in their degree of colour polymorphism, although the exact mechanisms driving such variation remain controversial. Here we address this fundamental question by considering information on all extant owls and recent advances in comparative methods in the frame of three mutually non-exclusive evolutionary scenarios. In addition, we study for the first time whether the evolution of influential ecological characters facilitated the evolution of colour polymorphism (or vice versa).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 47 publications
1
31
1
Order By: Relevance
“…Although Gloger’s rule has been verified in a number of animal populations, spanning from insects (Mayr, ) to birds (Burtt & Ichida, ; Delhey, ; Zink & Remsen, ) and mammals (Kamilar & Bradley, ; Stoner et al, ), its proximate mechanisms are still unclear. The main hypothesis links colour polymorphism with camouflage: dark individuals can be favoured in humid habitats because their colouration is cryptic where low environmental light and dense vegetation are common (Delhey, ; Passarotto et al, ). In the case of a nocturnal predator, like the barn owl, individuals displaying a darker plumage of the ventral body side can be favoured in cloudy, rainy and vegetated environments because their prey cannot easily detect their shape against the dark sky (i.e., when the moon is covered by the clouds or by the tree canopies), as also suggested by preliminary results showing that darker individuals are more efficient in hunting when moonlight is low (our unpublished results).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Gloger’s rule has been verified in a number of animal populations, spanning from insects (Mayr, ) to birds (Burtt & Ichida, ; Delhey, ; Zink & Remsen, ) and mammals (Kamilar & Bradley, ; Stoner et al, ), its proximate mechanisms are still unclear. The main hypothesis links colour polymorphism with camouflage: dark individuals can be favoured in humid habitats because their colouration is cryptic where low environmental light and dense vegetation are common (Delhey, ; Passarotto et al, ). In the case of a nocturnal predator, like the barn owl, individuals displaying a darker plumage of the ventral body side can be favoured in cloudy, rainy and vegetated environments because their prey cannot easily detect their shape against the dark sky (i.e., when the moon is covered by the clouds or by the tree canopies), as also suggested by preliminary results showing that darker individuals are more efficient in hunting when moonlight is low (our unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…Colour patterns are therefore driven by various, often opposing, selective forces, and thus represent compromises between such conflicting pressures acting locally (Cuthill et al, ). Because the strength of distinct selective pressures varies among habitats due to differences in climate and/or lighting conditions (Hill & McGraw, ; Passarotto, Parejo, Penteriani, & Avilés, ) and exposure to parasites and predators, as well as in breeding strategies and sexual behaviour (Cuthill et al, ; Hill & McGraw, ), geographical colour polymorphisms can arise.…”
Section: Introductionmentioning
confidence: 99%
“…Data available from the Dryad Digital Repository: <http://dx.doi.org/10.5061/dryad.n88k968> (Parejo et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Polymorphic species belonging to the order Strigiformes seem to have wider spatial niches than monomorphic species (Galeotti and Rubolini ). Indeed, recent comparative evidence has shown that owls living under more variable luminal conditions, i.e., species with diurnal and crepuscular habits and those inhabiting in a mixture of open and closed habitats, were more likely to show color polymorphism (Passarotto et al ), suggesting that different morphs may have an advantage in different environments. In one of these species, the tawny owl Strix aluco , annual morph frequencies vary over long time in relation to annual weather conditions (Galeotti and Cesaris 1996, Roulin et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Iris colour was scored as a binary variable as dark (including black or dark brown eyes) versus bright (including yellow, orange, red and light brown eyes); see Davidson et al () based on colour plates in del Hoyo et al (). Moreover, species were classified regarding activity rhythm as strictly nocturnal species versus species active also during the day or at dusk or dawn as in Passarotto et al (). Activity rhythm information was available for 201 species only (Supplementary material Appendix 1).…”
Section: Methodsmentioning
confidence: 99%